Use of a biothesiometer to measure individual vibration thresholds and their variation in 519 non-diabetic subjects. Issue 6433 (16th June 1984) - Bloom, S; Till, S; Sönksen, P; Smith, S
Abstract : A series of 519 non-diabetic subjects had vibration thresholds at three points measured using a biothesiometer. Thresholds appeared to be log normally distributed and increased with age. Centile charts of this relation were derived from the data giving a range for normal thresholds. The biothesiometer provides a quick and reliable assessment of vibration thresholds, which when related to the centile charts gives an objective measure of the progress of diabetic peripheral neuropathy.